Time-to-positivity of Mycobacterium avium complex in broth culture associates with culture conversion - Mingora, Christina M.; Garcia, Bryan A.; Mange, Kevin C.; Yuen, Dayton W.; Ciesielska, Monika; van Ingen, Jakko; Flume, Patrick A.; Dorman, Susan E. (BMC infectious diseases, 2022)
Background Mycobacterial time to positivity (TTP) in liquid culture media has predictive value for longer term outcomes in pulmonary tuberculosis, but has not been thoroughly studied in nontuberculous mycobacterial pulmonary disease. This study sought to evaluate for association between TTP and sputum culture conversion to negative in pulmonary disease caused by Mycobacterium avium complex (MAC). Methods Data from the CONVERT trial (NCT02344004) that evaluated efficacy of guideline-based-therapy with or without amikacin liposome inhalation suspension in adults with refractory MAC-PD ( Mycobacterium avium complex pulmonary disease) were analyzed. We evaluated TTP measures for sputum obtained prior to study treatment initiation and at monthly visits, assessing reproducibility of measures as well as association of TTP with culture conversion on treatment. Results Data from 71 participants with at least one screening visit TTP value were analyzed. For participants who provided more than one sputum sample at a given visit, there was moderate between-sample reliability, with median intraclass correlation coefficient 0.62 (IQR 0.50, 0.70). Median TTP at screening was longer in those participants who subsequently achieved vs. did not achieve culture conversion (10.5 [IQR 9.4] days vs. 4.2 [IQR 2.8] days, p = 0.0002). Individuals with culture conversion by study treatment month 6 were more likely to have a screening TTP > 5 days compared to those who did not achieve culture conversion (OR 15.4, 95% CI 1.9, 716.7, p = 0.0037) and had increasing TTPs over time. Conclusions TTP prior to and on treatment is associated with microbiological treatment response in patients with MAC-PD.